Practicality and effectiveness of student’s worksheet based on problem based learning to practice scientific literacy skill in matter acid and base - Maftukhatun Nimah; Aprianto Aprianto; Nurul Hidayati; Rusly Hidayah (Pascasarjana Universitas Negeri Medan, 2017)
The results of PISA's comperative studies show that the level of Indonesian science literacy is still low. From the results of the study stated that Indonesia is ranked 64 of 65 countries with a score of 382 science literacy on the study of natural science students. Necessary development of student’s worksheet to trace the ability of science literacy. The purpose of this research is to produce student’s worksheet based on problem based learning to trace the ability of science literacy which is practical and effective. The method used in this research is Research and Development (R&D). The results of the research have shown that student’s worksheet developed practical and effective. Student’s worksheet practicality seen from student response get good response equal to 94,99% with very good category. The effectiveness of student’s worksheet developed is seen from the gain score of the pre test and post test of the student.Key words: Student’s worksheet, practice, effective